Prácticas de enseñanzas en el área de matemática en primer año de Educación General Básica :estudio de caso: Unidad Educativa EMAÚS de Fe y Alegría - Tipán Gualotuña, Johanna Yessenia (2016)
The study explores teaching practices in the area of mathematics in first year of “Fe y Alegría” Educational Unit in order to meet the teaching management in the planning, implementation and evaluation practice, and determine their effectiveness or ineffectiveness. In the investigated institution difficulties in certain children was observed, about an low understanding of the activities in the area of mathematics which the study was necessary. The aim of this study was to identify the relationship between teaching practice and learning in the area of mathematics, for which a qualitative ethnographic study was applied. As research techniques participant observation and interviews were used, by applying observation sheets, interview guides and a field journal. The population was integrated by Professor freshman General Basic Education, the institution’s director and the first year’s group of children, which was carried out regular observations. As a result it was found that there is no clarity in the pedagogical trends that support the teaching practice, and neither classroom planning was evident. Classes were mainly passive although there was active participation of children sometimes; however the teacher-student interaction needs reinforcement and improvement within a framework of respect, cooperation and practical knowledge.